Birth weight and blood pressure in first-grade elementary school students: A preliminary study - Adrian Umboh; Stefanus Gunawan (Indonesian Pediatric Society, 2005)
Background Fetal programming theory reveals that low birthweight is associated with higher risks of hypertension and cardio-vascular diseases in the adulthood.Objective To study the difference in blood pressure among first-grade students of different birth weight groups.Methods A cross-sectional study was performed. Blood pressureof 214 healthy first-grade elementary school students (102 malesand 112 females) in Bunaken Subdistrict, Manado, Indonesia, wasmeasured using a standard sphygmomanometer with appropriatecuff for arm size. Two readings were taken. Parents were asked tocomplete a questionnaire concerning the information on birth weightand length and confirmed by retrieving the record on a growthchart and/or a maternal-child health book. The subjects were di-vided into 6 groups according to their birth weight. The differencesin blood pressure values between birth weight groups were exam-ined by ANOVA.Results Systolic blood pressures were significantly higher in the<2500 g birth weight group (100.73+9.99 mmHg vs. 93.70+8.29mmHg) and in the 2500-<3000 g birth weight group compared tothose of the 3500-<4000 g one (99.56+9.14 mmHg vs. 93.70+8.29mmHg) with a P of 0.048 and 0.014, respectively. There was nodifference between diastolic blood pressure and birth weight.Conclusion Our study showed that the lower birth weight grouptends to have a higher systolic blood pressure than that of childrenwith normal birth weight